Health indicators in the care for neurocritical patients - Elaine Aparecida Silva de Morais; Salomon Soriano Ordinola Rojas; Viviane Cordeiro Veiga (Universidade Federal do Ceará, 2014)
This study aimed to develop indicators to evaluate the care for neurocritical patients. Methodological study for development and validation of indicators of health evaluation, conducted on the Intensive Care Unit of a large hospital. The opinionated validation method was used, where seven experts (five nurses and two doctors) participated on the content analysis through operational manual from May to August 2012. The values obtained from the expert judgment were all above 80%, in which the literature reference was above 75%. The results revealed that all the indicators were considered valid as regards the agreement percentage. Therefore, it is possible to establish reliable indicators to evaluate the proposed care and establish the quality of the service. From the theoretical prerequisites, its use will support the control of assistance quality whilst collaborates with designing intervention plans.